Effect of Reduced Fluoroquinolone Use on Cephalosporin Use, Susceptibilities and Clostridioides difficile Infections - Callyn Mariah Wren; Jill Cowper; Nickie Greer; Laurel Goldin; Alicia Perry (MDPI AG, 2022)
Background: Overuse of fluoroquinolones has led to concerning rates of resistance, particularly among Gram-negative organisms. They are also highly implicated as a risk factor for Clostridioides difficile infection, and reports of other serious adverse events led to recommendations to restrict their use. Our health system began targeting the reduction in unnecessary fluoroquinolone prescribing in 2018, aiming to promote their safe and effective use. Broad-spectrum cephalosporins are often used as an alternative to fluoroquinolones. We sought to evaluate whether decreased fluoroquinolone use was associated with increased third- and fourth-generation cephalosporin use and whether these changes in utilization impacted other outcomes, including C. difficile infection (CDI) rates and susceptibilities among Gram-negative organisms. Methods: This retrospective descriptive analysis included adult patients who received a fluoroquinolone or broad-spectrum cephalosporin in a three-year time period across a large healthcare system. The primary objective was to evaluate the change in days of therapy (DOT) of fluoroquinolones and third- and fourth-generation cephalosporins. Secondary objectives included rates of resistance among common Gram-negative organisms, CDI, and analyses stratified by antibiotic indication. Results: Cephalosporin use increased by an average of 1.70 DOT/1000 PD per month (p < 0.001). Additionally, fluoroquinolone use decreased by an average of 1.18 DOT/1000 PD per month (p < 0.001). C. difficile infections decreased by 0.37 infections/10,000 patient-days per month (p < 0.001). Resistance to fluoroquinolones remained stable from 2018 to 2020, and a declining trend was observed in 2021. Conclusion: This study demonstrated that reduced fluoroquinolone use in a large healthcare system was associated with increased usage of broad-spectrum cephalosporins, decreased CDI and improvements in resistance patterns.